(3bUI jhSa GdUOjbs
(3ChdgG (B:s
(3fcJH NHQ jhSa dMSf Ef ENhI jhSa cGfJ JcQgg dCLd GdefGeGJ GdJicGf jQGgG GdJi JChjdgG Cf jchf dg SdWGf Ydjge s
(3BNQgG (B:s
(3CdG EfeG GdOfjG cefRd QGcH YTjkG hgh ai GdUHM QGMd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B197 - (3U(B237s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B327 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1065(3O(B) s
Keywords: (3GdJGQjNs